Differential Impacts of Water Table and Temperature on Bacterial Communities in Pore Water From a Subalpine Peatland, Central China - Tian, Wen; Xiang, Xing; Wang, Hongmei (Frontiers in Microbiology, 2021)
The level of water table and temperature are two environmental variables shaping soil bacterial communities, particularly in peatland ecosystems. However, discerning the specific impact of these two factors on bacterial communities in natural ecosystems is challenging. To address this issue, we collected pore water samples across different months (August and November in 2017 and May 2018) with a gradient of water table changes and temperatures at the Dajiuhu Peatland, Central China. The samples were analyzed with 16S rRNA high throughput sequencing and Biolog EcoMicroplates. Bacterial communities varied in the relative abundances of dominant taxa and harbored exclusive indicator OTUs across the different months. Despite these differences, bacterial communities showed high similarities in carbon utilization, with preferences for esters (pyruvic acid methyl ester, Tween 40, Tween 80 and D-galactonic acid γ-lactone), amino acids (L-arginine and L-threonine) and amines (phenylethylamine and putrescine). However, rates of carbon utilization (as indicated by average well-color development) and metabolic diversity (McIntosh and Shannon index) in May and August were higher than those in November. Redundancy analysis revealed that the seasonal variations in bacterial communities were significantly impacted by the level of the water table, whereas the temperature had a fundamental role in bacterial carbon utilization rate. Co-occurrence analysis identified Sphingomonas, Mucilaginibacter, Novosphingobium, Lacunisphaera, Herminiimonas, and Bradyrhizobium as keystone species, which may be involved in the utilization of organic compounds such as amino acids, phenols, and others. Our findings suggest that bacterial community functions were more stable than their compositions in the context of water table changes. These findings significantly expand our current understanding of the variations of bacterial community structures and metabolic functions in peatland ecosystems in the context of global warming and fluctuation of the water table..